Etika Komunikasi Digital Dalam Perspektif Qs. Al-Hujurāt: 11: Analisis Cancel Culture Di Indonesia - Auliya, Auliya; Nurul, Farisha; Mudhofar, Hanif (CONTEMPLATE: Jurnal Ilmiah Studi Keislaman, 2025)
Cancel culture on social media in Indonesia has developed rapidly and presents significant ethical challenges, as it can lead to social pressure, public humiliation, and damage to individual reputations, while simultaneously serving as a constructive mechanism for social control. The viral case of a TikTok user named Jule illustrates how public opinion can spread rapidly and influence societal perceptions. The academic concern arises from the limited research linking cancel culture practices with Islamic communication ethics, particularly the prohibition against mocking, belittling, or ridiculing others as stated in QS. Al-Hujurāt: 11 . This study employs a library research method by analyzing classical exegeses (Al-Ṭabarī, Ibn Katsīr) and contemporary interpretations (Quraish Shihab, Hamka), alongside an examination of viral digital communication practices, to interpret the application of the Digital Communication Ethics concept in social media contexts. The findings indicate that cancel culture can be ethically constructive if implemented proportionally, based on verified facts, and aimed at corrective purposes, while maintaining human dignity. Ethical practice emphasizes education, reflection, and accountability rather than mere punishment or public humiliation. These results underscore the relevance of Qur’anic values as a normative foundation for responsible, just, and dignified digital communication, while providing an ethical framework for academics and the public to evaluate and manage online interactions effectively